2009
DOI: 10.1017/s0029665110004702
|View full text |Cite
|
Sign up to set email alerts
|

The breads, cereals and potato food group: perceptions of average portions in Ireland

Abstract: Current healthy eating guidelines recommend at least six servings from the breads, cereals and potato group of the food pyramid, depending on energy requirements (age, gender and activity levels) (1). However, there is evidence that the rise in obesity is occurring in parallel with consumption of larger portion sizes (2). Differences in size between portions that are normally consumed and those that are recommended may confuse individuals who are attempting to follow healthy eating guidelines. The aim of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
(1 reference statement)
0
3
0
Order By: Relevance
“…Consumers also pointed out that it was easy to limit portion sizes of foods that were ‘filling’, such as porridge or mashed potatoes, while this was much more difficult for foods that were not ‘filling’, such as rice or muesli. Some consumers (mainly men) described portions of these latter foods that were much bigger than the range of portions we developed up to the limit of 921 kJ (220 kcal) ( 13 , 17 ) .…”
Section: Develop Personal Skillsmentioning
confidence: 97%
See 2 more Smart Citations
“…Consumers also pointed out that it was easy to limit portion sizes of foods that were ‘filling’, such as porridge or mashed potatoes, while this was much more difficult for foods that were not ‘filling’, such as rice or muesli. Some consumers (mainly men) described portions of these latter foods that were much bigger than the range of portions we developed up to the limit of 921 kJ (220 kcal) ( 13 , 17 ) .…”
Section: Develop Personal Skillsmentioning
confidence: 97%
“…The same two food displays were used to seek feedback from over 1000 adult shoppers in advantaged and disadvantaged areas of Dublin. Over three quarters of shoppers preferred the second option of a range of portion sizes because these were closer to the portions they considered ‘average’ for the different types of food in this group ( 13 , 17 ) . Many consumers suggested that the option where all portions provided approximately 418 kJ (100 kcal) consisted of ‘parts of a portion’ that would possibly be appropriate for children but not for adults ( 18 ) .…”
Section: Develop Personal Skillsmentioning
confidence: 99%
See 1 more Smart Citation